THE RELATIONSHIP BETWEEN BODY MASS INDEX AND GROSS MOTOR DEVELOPMENT IN TODDLERS AGED (2-5 YEARS) - Nisak, Mufidatun (jfpublisher, 2025)
Introduction. Toddlers with a low Body Mass Index or poor nutrition tend to experience motor delays due to a lack of energy and muscle mass needed for physical activity. On the other hand, toddlers with a high Body Mass Index or obesity often face obstacles in moving due to excessive body weight, which can reduce balance, agility and physical endurance. The aim of this research was to determine the relationship between body mass index and gross motor development in Tegalrejo Village, Merakurak. Methods. This research used a correlational analytical method with a cross sectional approach with a population of 206 toddlers aged 2-5 years. The sampling method used simple random sampling technique to obtain a sample of 136 toddler respondents aged 2-5 years. The instruments used were a stature meter, scales and a Denver II observation sheet using the Spearman's rho correlation test. Results&Analysis. The results of the research carried out after being analyzed using the Spearman's rho test with a significance level of α = < 0.05 obtained a value of ρ = 0.000 < 0.05, so H1 was accepted. Based on the results of this data analysis, it can be concluded that there is a significant relationship between body mass index and gross motor development in toddlers aged (2-5 years) in Tegalrejo Village, Merakurak. Conclusion. There is a relationship between body mass index and gross motor development in Tegalrejo Merakurak Village. Based on this, the better the body mass index, the more normal gross motor development in toddlers.